Evaluation of Feeding High Proportion Concentrates Containing Tofu Waste On Nutrient Consumption, Milk Production and Body Condition Score of Dairy Goat in Smallholder of Yogyakarta - Suranindyah, Yuni (2018)
The study was done to investigate the effect of feeding high proportion concentrate containing tofu waste on nutrient consumption, milk production, body condition score, and postpartum mating of dairy goat. Data were collected from 30 lactating goats in small farms in Sleman region, Yogyakarta province, Indonesia. The goats were fed two types of diet, respectively consisted of Calliandra calothyrsus and wheat pollard as diet for farm A, Calliandra calothyrsus, wheat pollard and tofu waste as diet for farm B. The proportion of concentrates in farm A was 20% and in farm B was 55% on dry matter basis. The data were collected to obtain feed and nutrient consumption, milk production, body condition score and the period of postpartum mating. All data were statistically analysed by T-test. The results showed that feeding high proportion concentrates containing tofu waste was significantly (P<0.05) decreased dry matter and crude protein intake but no effect on crude fibre and total digestible nutrient consumption. There was no effect on milk production and body condition score, indicated that high concentrate feed could provide sufficient nutrient for lactating goat. The period of postpartum mating was longer in goat fed high concentrate diet. Body condition score did not affect postpartum mating of goats but tends to support energy for milk production.